Analysis of root and canal morphology of maxillaryfirst and second molars among malay ethnic in the malaysian population with the aid of cone-beam computed tomography: A retrospective study - Abd Rahman, Nadzirah; Halim, Mohamad Syahrizal; Khamis, Mohd. Fadhli; Abd Ghani, Huwaina (European Journal of General Dentistry, 2020)
Aim: This study aimed to investigate the root and canal morphology of permanent maxillaryfirst and second molars using cone-beam computed tomography (CBCT) imaging. Materials and Methods: This study evaluated the CBCT images of 480 maxillaryfirst molars and 536 maxillary second molars from 268 patients who received CBCT scanning for various procedures. The number of roots, prevalence of the second mesiobuccal (MB2) canal in the mesiobuccal root, its association with gender, and the prevalence of bilateral MB2 canals were evaluated. Descriptive statistics was used to evaluate the prevalence, while Chi-square test was used to assess the association between the prevalence of MB2 canal and gender with a significance level set at P < 0.05 and P < 0.001. Results:Majority of maxillaryfirst (97.7%) and second molars (80.0%) were presented with three roots. MB2 canals were found in 59.9% and 35.2% of maxillaryfirst and second molars, respectively. The prevalence of MB2 canals among male patients was significantly higher in both maxillaryfirst (P < 0.05) and second molars (P < 0.001). Bilateral MB2 canals were seen in 76.2% and 58.3% of maxillaryfirst and second molars, respectively. Conclusions: MB2 canal was common among Malay ethnic with the prevalence of approximately 60% and 35% in maxillaryfirst and second molars, respectively. Our findings will increase the knowledge and awareness of dental clinicians to be more vigilant in identifying the MB2 canal to ensure complete cleaning and obturation of all root canals during root canal treatment.
Keywords: Cone-beam computed tomography; Malay; maxillaryfirst molar; maxillary second molar; root and canal morphology